Evaluating the implementation process of a participatory organizational level occupational health intervention in schools - Roosmarijn M. C. Schelvis; Noortje M. Wiezer; Birgitte M. Blatter; Joost A. G. M. van Genabeek; Karen M. Oude Hengel; Ernst T. Bohlmeijer; Allard J. van der Beek (BMC, 2016)
Abstract Background The importance of process evaluations in examining how and why interventions are (un) successful is increasingly recognized. Process evaluations mainly studied the implementation process and the quality of the implementation (fidelity). However, in adopting this approach for participatory organizational level occupational health interventions, important aspects such as context and participants perceptions are missing. Our objective was to systematically describe the implementation process of a participatory organizational level occupational health intervention aimed at reducing work stress and increasing vitality in two schools by applying a framework that covers aspects of the intervention and its implementation as well as the context and participants perceptions. Methods A program theory was developed, describing the requirements for successful implementation. Each requirement was operationalized by making use of the framework, covering: initiation, communication, participation, fidelity, reach, communication, satisfaction, management support, targeting, delivery, exposure, culture, conditions, readiness for change and perceptions. The requirements were assessed by quantitative and qualitative data, collected at 12 and 24 months after baseline in both schools (questionnaire and interviews) or continuously (logbooks). Results The intervention consisted of a needs assessment phase and a phase of implementing intervention activities. The needs assessment phase was implemented successfully in school A, but not in school B where participation and readiness for change were insufficient. In the second phase, several intervention activities were implemented at school A, whereas this was only partly the case in school B (delivery). In both schools, however, participants felt not involved in the choice of intervention activities (targeting, participation, support), resulting in a negative perception of and only partial exposure to the intervention activities. Conditions, culture and events hindered the implementation of intervention activities in both schools. Conclusions The framework helped us to understand why the implementation process was not successful. It is therefore considered of added value for the evaluation of implementation processes in participatory organizational level interventions, foremost because of the context and mental models dimensions. However, less demanding methods for doing detailed process evaluations need to be developed. This can only be done if we know more about the most important process components and this study contributes to that knowledge base. Trial registration Netherlands Trial Register NTR3284 .